Transmigration of Javanese People to Ujung Batu IV Village, Sosa District Padang Lawas Regency, North Sumatra 1982-2022 - Siregar, Martina Suryanami; Anatona, Anatona; Djalius, Yusmarni (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study aims to examine the dynamics of transmigrant life in Ujung Batu Village IV, as well as the patterns of social interaction and economic changes experienced by these transmigrants. The method used in this study is a historical method through four stages: heuristics, source criticism, interpretation, and historiography. The results of this study indicate that the transmigration program in Ujung Batu Village IV, which began in 1982, was an effort to address overpopulation on Java Island and ensure equitable development. Despite facing various challenges such as a lack of initial information, minimal basic infrastructure, and difficulties in social and cultural adaptation, the program showed significant progress, especially after the implementation of the PIR-KKPA pattern. This pattern encouraged partnerships with plantation companies, opened access to productive land, provided training, and marketed crops, which directly improved the economic welfare of transmigrants. Furthermore, harmonious social integration occurs between ethnic groups through social interaction, education, and intermarriage, creating an independent and competitive community.